Relationship of Third Party Funds and Financing on The Profitability of Islamic Banks in Indonesia For The 2017-2021 Period: English - Kaban, Putri Rona Wulandari Br; Pohan, Selamat (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam Syarifuddin Lumajang, 2023)
The purpose of this research is to find out and analyze the relationship between third party funds (DPK) and financing on the profitability of Islamic banks in Indonesia. The type of research in this paper is quantitative research and the data used is a type of secondary data. The population used in this study is the financial statements of Islamic commercial banks in Indonesia published by the Financial Services Authority (OJK). Data analysis techniques with descriptive tests, normality tests, multicollinearity tests, heteroscedasticity tests, autocorrelation tests, correlation coefficient tests and coefficient of determination tests (R2). Processing of data using the SPSS program version 22.0. The results of this study are third party funds (DPK) have a negative relationship to the profitability of Islamic banks in Indonesia, which is -0.737 or -73.7%, while financing has a strong positive relationship to the profitability of Islamic banks in Indonesia, which is equal to 0.750 or 75%. , as well as third party funds (DPK) and financing have a strong positive relationship to the profitability of Islamic banks in Indonesia, which is equal to 0.761 or 76.1%.